PROSES PEMEROLEHAN BAHASA PADA ANAK USIA DINI - Purwati, Purwati; Japar, Muhammad (Universitas Muhammadiyah Magelang, 2009)
Language is a communication tool to convey and receive messages from individual or group to another person or group of persons. Language acquisition is essentially influenced by factors within individuals and individuals outside. To optimize the development of early childhood language need for stimulation from the environment and not just rely on the existence of internal factors of children. Educators, including parents and teachers must master aspects of the development and characteristics of children so that the stimulation that will produce optimal results.